Authentication of Digital Video Encryption - Mohsen, Asmaa Hasan; Shaker, Shaimaa Hameed (Iraqi Journal of Science, 2022)
The security of multimedia data becoming important spatial data of monitoring systems that contain videos prone to attack or escape via the internet, so to protect these videos used proposed method combined between encryption algorithm and sign algorithm to get on authenticated video. The proposed encryption algorithm applied to secure the video transmission by encrypt it to become unclear. This done by extract video to frames and each frame separate to three frames are Red, Green, and Blue, this frames encrypt by using three different random keys that generated by a function for generating random numbers, as for sign algorithm applied for authentication purpose that enable the receiver from sure of the identity of the sender and provide secure communication between two communication parties.In the proposed method applied compression method before encryption algorithm on video by using discrete wavelet transform (DWT) to facilitation work of encryption algorithm because compression less size of video and this make execution time of encryption algorithm faster. The decryption algorithm and decompression method are big prove to success of proposed method that give target video without any noise, besides that has been verified from performance of proposed method using several quality measures performance of proposed method.